Enhancement of (211)At Uptake via the Sodium Iodide Symporter by the Addition of Ascorbic Acid in Targeted α-Therapy of Thyroid Cancer - Watabe, Tadashi (J Nucl Med, 2019)
(211)At is an α-emitter that has similar chemical properties to iodine and is used in targeted α-therapy. In the present study, we added ascorbic acid (AA) to (211)At solution to increase the radiochemical purity of astatide and evaluated its efficacy against differentiated thyroid cancer, which is characterized by the expression of sodium/iodide symporter (NIS). Methods: Crude (211)At solution (AA(−)) and (211)At solution treated with AA (AA(+)) were prepared. Uptake by the thyroid was compared between the 2 solutions in normal male Wistar rats (n = 6). Cellular uptake in K1-NIS cells was analyzed under the AA(+) and AA(−) conditions. AA(+) was injected at 3 doses into K1-NIS xenograft mice: 1 MBq (n = 6), 0.4 MBq (n = 6), and 0.1 MBq (n = 6), and vehicle was injected into control mice (n = 6). The treatment effects were compared among the 4 groups. Results: Uptake by the thyroid was significantly enhanced in rats injected with the AA(+) as compared with those injected with AA(−). Cellular uptake analysis showed significantly increased uptake of (211)At by the K1-NIS cells under the AA(+) condition as compared with the AA(−) condition. In the mouse xenograft model, the K1-NIS tumors showed significant accumulation of (211)At at 3 and 24 h after administration (22.5 ± 10.4 and 12.9 ± 6.8 percentage injected dose, respectively). Tumor growth was immediately inhibited in a dose-dependent manner after administration of (211)At. In the survival analysis, the (211)At groups (0.1, 0.4, and 1 MBq) showed significantly better survival than the control group. Conclusion: Uptake of (211)At was enhanced in differentiated thyroid cancer cells as well as the normal thyroid using (211)At solution treated with AA. The method also showed dose-dependent efficacy against the K1-NIS xenografts, suggesting its potential applicability to targeted α-therapy.